The Relationship Between Scientific Literacy Skills and Self-Efficacy of Junior High School Students in Science Learning - Aulya Putri, Winda; Fernando, Adam; Oprasmani, Elfa (UNIVERSITAS NEGERI MEDAN, 2025)
This study aimed to determine the level of scientific literacy skills and self-efficacy of junior high school students in science learning. This research was conducted through the administration of a scientific literacy test and a self-efficacy questionnaire. The research instrument consisted of a scientific literacy test in the form of essay questions that measured three indicators of scientific competence, and a self-efficacy questionnaire adapted from Bandura with indicators of magnitude, strength, and generality. The results showed that students' scientific literacy level was in the very low category, with the majority of students (81.1%) only reaching the nominal literacy level. It indicates that although students can recognize basic concepts in science, they still have difficulty explaining scientific phenomena and using scientific evidence logically. Meanwhile, students' self-efficacy level is generally in the moderate category, although it is still relatively low in some indicators, such as generality. The correlation test shows a significance value of 0.305 > 0.05 with a Pearson correlation coefficient of 0.098, which means there is no significant relationship between scientific literacy skills and self-efficacy. The coefficient of determination of 0.0096 indicates that the contribution of scientific literacy to self-efficacy is only 0.96%, while other factors influence the other 99.04%. The analysis showed no significant relationship between students’ scientific literacy skills and self-efficacy, as scientific literacy contributed only minimally and was largely influenced by other factors.